TRANSFORMATION OF ESCHERICHIA COLI WITH pET21A+ AND EXPRESSION OF THE NOVEL ANTIMICROBIAL PEPTIDE INDOLICIDIN - K. PANNEER SELVAM; B. ANNAMALAI; G. NAMBIRAJAN; C.S. SHOBANA (International Journal of Pharma and Bio Sciences, 2014)
Indolicidin is an antimicrobial cationic peptide naturally present in the bovine neutrophils. In this study, transformed Escherichia coli cells were employed for greater and cost effective production of indolicidin. Four strains of E. coli [C41 (DE3), C43 (DE3), C41 (DE3) pLysS & C43 (DE3) pLysS] were transformed with recombinant plasmid pET21A+ carrying the indolicidin gene and were successfully expressed for indolicidin in the presence of the inducer isopropyl β-D-1-thiogalactopyranoside (IPTG). Further, the production of indolicidin was confirmed by detecting the 2 KDa indolicidin band on sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE).